Conservation and curation: Theoretical and practical issues in the making of a national collection of British Music Videos 1966–2016 - Emily Caston (Alphaville: Journal of Film and Screen Media, 2020)
This article identifies and examines the research methods involved in curating a national collection of British music videos for the British Film Institute and British Library in relation to existing scholarship about the role of the curator, the function of canons in the humanities, and the concept of a hierarchy of screen arts. It outlines the process by which a theoretical definition of “landmarks” guided the selection of works alongside a commitment to include a regionally and socially diverse selection of videos to reflect the variations in film style of different music genres. The article also assesses the existing condition of British music video archives: rushes, masters, as well as documents and digital files, and the issues presenting academics and students wishing to study them. It identifies the fact that music video exists in the gaps between two disciplines and industries (popular music studies / the music industry and film and television studies / the screen industries) as an additional challenge to curators of the cultural form, alongside complex matters of licensing and formats.